Mechanical properties and crack deflection mechanisms in 3D-Printed porous geopolymers with cellular structures - Ali Rezaei Lori; Mehdi Mehrali (Virtual and Physical Prototyping)
This study focuses on using helical design patterns via 3D printing to create geopolymer with a highly porous structure in order to enhance their strength-density relationship and fracture properties. In this regard, to create porous structure, different pitch angles and infill densities were chosen, and mechanical and fracture properties were examined. The results of mechanical strength tests revealed that while the pitch angle does not significantly affect compressive strength, flexural strength is improved by implementing a low pitch angle helical structure, which leads to the strength-density relationship improvement. Additionally, the work of fracture results demonstrated an enhancement for samples with low pitch angles, such as α15° and α30°, compared to cast and non-directional printed samples. The digital image correlation and fracture surface analysis showed several fracture mechanisms, predominantly crack deflection and twisting, in samples with low pitch angles, which contributes to the observed improvements in the work of fracture.